Modeling Process-Related Duties with Extended UML Activity and Interaction Diagrams - Schefer, Sigrid; Strembeck, Mark (Electronic Communications of the EASST, 2011)
Business processes are an important source for the engineering of customized software systems. In this context, the definition, monitoring, and enforcement of the duties associated with different tasks in a business process is one important factor to ensure compliance of an IT system with certain laws and regulations. In this paper, we present a UML2 extension for an integrated modeling of business processes and process-related duties. In particular, our extension allows for the modeling of duties and associated tasks in business process models.